Cameroon : Poverty Reduction Strategy Paper-Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The growth rate of agriculture in Cameroon was estimated at 3.3 percent in 2006, compared with 2.7 percent in 2005. This is owing to increased activity in the food agriculture sector (4.3 percent) and in forestry and logging (4.0 percent). Livestock farming and fisheries, on the one hand, grew by 3 percent and 2 percent, respectively. Industrial and commercial agriculture, on the other hand, experienced a slowdown, on the one hand, with a growth rate of -2.3 percent in 2006 compared with 1.7 percent in 2005.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet